2014
DOI: 10.1038/ncomms4582
|View full text |Cite
|
Sign up to set email alerts
|

Waving potential in graphene

Abstract: Nanoscale materials offer much promise in the pursuit of high-efficient energy conversion technology owing to their exceptional sensitivity to external stimulus. In particular, experiments have demonstrated that flowing water over carbon nanotubes can generate electric voltages. However, the reported flow-induced voltages are in wide discrepancy and the proposed mechanisms remain conflictive. Here we find that moving a liquid-gas boundary along a piece of graphene can induce a waving potential of up to 0.1 V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
280
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 308 publications
(318 citation statements)
references
References 30 publications
7
280
3
3
Order By: Relevance
“…[17] Since an onlinear response of the induced voltage to the flowing velocityw as observed, momentum transfer and streaming potentialm odels could not be used to interprett he experimental results. [20] Unlike the previous work where the graphene was completely immersedi nt he water,h ere the fluidic nanogenerator was only partly immersed, indicating ad ifferent workingm echanism. But the flowing voltage generation of the graphene was questioned in the next year.…”
Section: Nanogenerators Based On Graphenementioning
confidence: 82%
“…[17] Since an onlinear response of the induced voltage to the flowing velocityw as observed, momentum transfer and streaming potentialm odels could not be used to interprett he experimental results. [20] Unlike the previous work where the graphene was completely immersedi nt he water,h ere the fluidic nanogenerator was only partly immersed, indicating ad ifferent workingm echanism. But the flowing voltage generation of the graphene was questioned in the next year.…”
Section: Nanogenerators Based On Graphenementioning
confidence: 82%
“…This result was attributed to the absence of molecular reorientation on graphene with a chemically homogenous surface. Recently, Yin et al showed that the droplets of ionic liquid can easily slide on a graphene surface [86] and, in a much more interesting result, they found that the movement of the liquid−solid−gas three-phase boundary on a graphene surface can generate electricity [86,87]. All these results suggest that graphene is a promising material to construct efficient and intelligent channels for liquid flow.…”
Section: Frictional Interaction Between Liquid and 2d Materialsmentioning
confidence: 99%
“…However, the dispersion was not stable (easily coagulate) due to the fact that the graphene may be slightly charged in NaCl aqueous solution (Figure S8, Supporting Information). This phenomenon may be closely related with the selective adsorption of Na ions . Due to its uniquely charged feature, the graphene prepared in the present method can be used as adsorbent for the removal of anionic and cationic dye molecules.…”
Section: Resultsmentioning
confidence: 79%